2012
DOI: 10.1007/s00432-012-1322-z
|View full text |Cite
|
Sign up to set email alerts
|

A nine-gene signature predicting clinical outcome in cutaneous melanoma

Abstract: Our gene score defines patient risk and need for therapy in melanoma. The score has the potential to be utilized in clinical routine, since it is quantitative, robust, simple, and independent of AJCC stage and sample purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 35 publications
0
55
1
2
Order By: Relevance
“…Five genes from a combined list from Conway et al and Jewell et al overlap with Winnepenninckx et al, and osteopontin overlapped between the Conway/Jewell and Gschaider et al studies. None of the 92 genes originally reported to be associated with OS in Brunner et al [58] and further assessed in a follow-up study [59] overlapped with genes reported in the other studies, though we note that none of the other studies defined genes directly associated with OS.…”
Section: Expression Of Protein-coding Genesmentioning
confidence: 57%
See 1 more Smart Citation
“…Five genes from a combined list from Conway et al and Jewell et al overlap with Winnepenninckx et al, and osteopontin overlapped between the Conway/Jewell and Gschaider et al studies. None of the 92 genes originally reported to be associated with OS in Brunner et al [58] and further assessed in a follow-up study [59] overlapped with genes reported in the other studies, though we note that none of the other studies defined genes directly associated with OS.…”
Section: Expression Of Protein-coding Genesmentioning
confidence: 57%
“…Interestingly, another recent study, which defined a pro-invasive HOXA1 transcriptional signature, found that patients from the Winnepenninckx et al study with a ‘high’ HOXA1 signature had poor DMFS, adding an intriguing underlying transcriptional mechanism to those original expression findings, though they did not note if DNA repair pathway genes were highly represented in their signature [57]. A second primary cutaneous melanoma expression profiling study identified 92 genes associated with OS [58], and a subsequent follow-up study, which further assessed these 92 genes, reported a 9-gene signature (6 protective and 3 unfavorable) associated with OS in a 91 patient cohort [59]. A recent report utilized serial analysis of gene expression (SAGE) to identify differentially expressed transcripts between 116 primary tumors that had not metastasized (stage I/II) and 72 primary tumors that had already spread at initial diagnosis (stage III/IV) [60].…”
Section: Expression Of Protein-coding Genesmentioning
confidence: 99%
“…Web-based gene ontology analysis tools revealed that genes related to the biologic processes of tissue development and epithelial differentiation, as well as cell junction-related genes, are highly represented. In comparison, a subsequently reported signature discovered by Harbst and colleagues reflects genes related to wound/immune responses, DNA repair, and cell-cycle, whereas a subsequently reported 9-gene signature from Brunner and colleagues contains genes encoding small secretory peptides and cell invasion-related extracellular and cytoskeletal genes (24,25). Of note when directly comparing the gene panels is that CXCL14 was the only gene identified in the current analysis that was included in those genetic signatures.…”
Section: Discussionmentioning
confidence: 99%
“…The queried genes are KRT9, KBTBD10, DCD, ECRG2, PIP, SCGB1D2, SCGB2A2, COL6A6, and HES6, and the genetic signatures were validated among a cohort of 44 additional melanomas (Brunner et al 2013). Several of the genes associated with metastasis encode stromal proteins, suggesting the importance of the tumor's microenvironment in the clinical course of melanoma.…”
Section: Genomic Expression Patterns Associated With Aggressive Clinimentioning
confidence: 99%